Psychological Factors of Religion Traveler and Decision to Visit - Bashori Filmi; Ade Yuliar; Fathurrohman Husen (Institut Agama Islam Negeri Bengkulu, 2022)
This study aims to determine the effect of psychological factors on the decision to visit. The decision to visit is the dependent variable, while motivation, perception, learning, and belief are independent variables. The method used in this research is quantitative research methods. This study used primary data using research data collection techniques and online questionnaires through Google Forms. Using Roscoe's theory, this study uses a purposive sampling technique to determine the number of respondents. The sample in this study was 100 respondents. The analysis was used using a multiple linear regression test through the SPSS 25 program. The analysis shows that factors of motivation, perception, learning and belief together influence the decision of tourists to choose tour religion. However, partial, the fourth-factor perception and belief, has influence significant and dominant decision visit tourists in choosing religious tourism.